New considerations in the design of clinical trials of acute kidney injury - Md Ralib, Azrina; Pickering, John W.; Nejat, Maryam; Endre, Zoltan H. (Future Science, 2011)
Acute kidney injury is a common and frequently fatal disease without an effective early intervention. The translation of promising experimental treatments to effective clinical trials has been hampered by the lack of a means to detect acute kidney injury early. Novel biomarkers of kidney injury have made early intervention possible and the first early intervention trial has been run. Emerging issues are the timing of biomarker measurement, the relationship of biomarker concentration with baseline renal function, and determining a primary outcome that best reflects renal function. A new generation of early intervention trials with increased prospects of finding effective therapies are now possible utilizing currently available novel biomarkers. Proposed new outcome measures will decrease the likelihood of negative trials as a result of poor design.